Les barrages du Rio Madeira : géopolitique d’une intégration transfrontalière Brésil-Bolivie-Pérou - Céline Broggio; Marcio Cataia; Martine Droulers; Juan-Pablo Pallamar (Bulletin de l’Association de Géographes Français)
The relaunch of hydroelectric dams construction in the Brazilian Amazon reopens the question of cross-border relations and cooperation with the countries of the Amazon basin, particularly Bolivia and Peru. If the Brazilian dams Santo Antonio and Jirau on the Madeira River (Rondônia) create social and environmental conflicts, they also create the opportunity for laying the foundations of a cross-border cooperation at a regional level.